(3GdEYdGe h GdeLJeY (B/s - (3GdMOjOj, efi SYjOs; (3EeGe Ydis ((3GdbGgQI (B:s (3GdOGQ GdeUQjI GddHfGfjI ,s, 2022)
(3jJfGhd GdcJGH YOOG ef GdehVhYGJ GdYGeI GdJj JajO OQGSi Ydhe GdGYdGe h afhfg h cPdc eeGQSi GdYed GdEYdGej h NGUI ef jYedhf aj GdeLGd GdHQGeLi h MedGJ GdhYjI h GdJShjb GdGLJeGYj MjK JWQbJ GdHGMKJGf dYOO ef GdehVhYGJ GdGSGSjI ajeG jYQa HGdGJUGd GdGbfGYj h GdPj jeKd GdQcjRI GdGSGSjI dJaYjd OhQ GdGYdGe aj GdJfejI h GdJMOjKs
Keywords: (3GdEYdGes; (3GdYdhe GdELJeGYjIs